2005
DOI: 10.1158/1078-0432.ccr-04-2106
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Evaluation of Gemcitabine Combination Regimens for Application in Acute Myeloid Leukemia

Abstract: The DNA antimetabolite gemcitabine is an anticancer agent with shown preclinical and clinical utility and a low toxicity profile. In this study, we sought to identify and optimize drug partners for binary and tertiary combinations with gemcitabine for use in the treatment of acute myelogenous leukemia (AML). Drug interaction was assessed by growth inhibition assay with metabolic end points. The combination index method was used to evaluate combinations of gemcitabine with fludarabine, paclitaxel, chlorambucil,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…Finally, we used cell types (ovarian and pancreatic cancer) that are known to be responsive to topo I poisons and gemcitabine. Consistent with our results, antagonism has also been reported when U937 human leukemia cells are simultaneously exposed to gemcitabine and SN-38 (Shanks et al, 2005), although the mechanism of this antagonism was not examined. Several experiments were performed to assess the mechanism of antagonism observed in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, we used cell types (ovarian and pancreatic cancer) that are known to be responsive to topo I poisons and gemcitabine. Consistent with our results, antagonism has also been reported when U937 human leukemia cells are simultaneously exposed to gemcitabine and SN-38 (Shanks et al, 2005), although the mechanism of this antagonism was not examined. Several experiments were performed to assess the mechanism of antagonism observed in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Synergism, additive effects, or antagonism was assessed using the Chou-Talalay method (42,60) and Calcusyn software (Biosoft). The extent of apoptosis in drug-treated samples was quantified as a percentage of Annexin V -positive cells over the total cell population; apoptosis in DMSO-treated controls was negligible.…”
Section: Discussionmentioning
confidence: 99%
“…57 Preclinical studies have suggested a synergism between gemcitabine and fludarabine. 8 For these reasons, we evaluated the addition of gemcitabine (G) to our standard fludarabine (F) - melphalan 140 mg/m 2 (M140) reduced-intensity conditioning regimen (FM140) 9 in patients with relapsed and refractory HL undergoing allo-SCT. Initial results of this study were presented previously.…”
Section: Introductionmentioning
confidence: 99%